(untitled) (Scientific journal of the Fergana State University, 2023)
In the paper a non local problem for a model parabolic hyperbolic equation is researched. The third boundary condition and an integral condition are given in the parabolic part of the domain, and a shifting condition is given in the hyperbolic part of the domain. The existence and uniqueness of the solution of the problem is proved